Impact of Oil Price Tumble in 2020 and US Retrenchment on the Stability of the Gulf Region. Issue 2 (September 2020) - Banerjee, Somen
The Indo-Pacific blends a multitude of regions and melds a panoply of security architectures. Some regions are peaceful, with occasional spurts in environmental disasters and non-traditional security challenges, while others are typified by instability and security-dilemma. The Gulf region is a unique arena of the Indo-Pacific, that has stirred a virulent concoction of the oil economy, regional rivalry and US hegemony. Over a century ago, oil discovery has not just made the region wealthy but has also transformed it into a veritable Western Lake. But lately, two significant developments have begun to unravel this homeostatic condition—a tumble in oil prices and US retrenchment from the region. This is likely to have a profound influence on the regional security order. This article examines the role of oil in defining the security architecture of the region. It establishes the effect of demand-supply imbalance and the oil-price-futures on the economy of Gulf countries. Finally, it evaluates the impact of US retrenchment, and the 2020 oil price tumble, on the long-term stability of the region.